Inorganic Geochemical Reactions During In Situ Oxidation of Chlorinated Solvents Using Potassium Permanganate - Maldaner, Carlos H.; Hirata, Ricardo; Bertolo, Reginaldo A. (Águas Subterrâneas, 2009)
The potential success of In situ Chemical Oxidation (ISCO) using potassium permanganate as a remediation technology to treat PCE and TCE groundwater impacts was previously demonstrated by several authors, showing that permanganate can completely mineralize chlorinated solvents into neutral by-products soluble ion salts, producing carbon dioxide (CO2) and manganese oxides, and leading to changes in the groundwater pH. Therefore, the injection of high amounts of oxidants into the aquifer can also change the overall aqueous geochemistry, affecting the concentrations of anions and cations in solution, creating a potential of increasing metals mobility, leading to coprecipitation of some metals species and also increasing adsorptive surfaces due to oxides precipitation. This paper shows the importance of batch experiments and pilot scale remediation field tests in the development of site conceptual geochemical models and how these tools can prevent any significant geochemical modification in the groundwater condition, leading to the potential generation of secondary contaminant plumes during ISCO implementation.